Evaluasi Jaringan DCS1800 dan U2100 Indoor Base Station Existing di Gedung Bertingkat Wilayah Kota Malang - Muhammad Rizal Azizul Hakim (Politeknik Negeri Malang, 2017)
This study aims to determine the Rx Level value on each floor in the building and determine the omni ceiling antenna coverage. Calculation of coverage using the Free Space Loss (FSL) method and measurement with a walk test. Calculation of coverage with the DCS1800 and U2100 networks uses the FSL method to determine the coverage distance per omni ceiling antenna. The result is the farthest distance is 24 meters and the closest distance is 4 meters and the average distance per omni ceiling antenna is 8 meters. As for the results of the walk test on the DCS1800 network, very good results were obtained for the Rx Level value on all floors in the building and for the U2100 network, the results were not good for the Rx Level value on all floors in the building, so it was necessary to evaluate at several points. antenna to improve the quality of the indoor network becomes feasible. In the results of the walk test on the DCS1800 network and the U2100 network, there are several areas in the building that experience bad Rx Level values ??due to poor transmission power so it is necessary to add 1 antenna sector.